Rumination, posttraumatic stress disorder, and mood symptoms in borderline personality disorder - Dell'Osso L (Dove Medical Press, 2019)
Liliana Dell’Osso,1 Ivan M Cremone,1 Barbara Carpita,1 Valerio Dell’Oste,1 Dario Muti,1 Gabriele Massimetti,1 Stefano Barlati,2 Antonio Vita,2 Andrea Fagiolini,3,4 Claudia Carmassi,1 Camilla Gesi11Department of Clinical and Experimental Medicine, University of Pisa, Pisa, Italy; 2Department of Clinical and Experimental Sciences, University of Brescia, Brescia, Italy; 3Department of Mental Health, University of Siena, Siena, Italy; 4Department of Molecular Medicine, University of Siena, Siena, ItalyBackground: The interrelationship between mood disorders and borderline personality disorder (BPD) has been long debated in the literature. Increasing attention has also been paid to the relationship between posttraumatic stress disorder (PTSD) and BPD, as well as to the role of rumination in the development and severity of BPD. This study aims to evaluate the association of rumination, PTSD, and mood spectrum among patients with BPD with or without comorbid mood disorders.Methods: Fifty patients with BPD and 69 healthy controls were assessed with the Structured Clinical Interview for the Diagnostic and Statistical Manual of Mental Disorders 5, MoodSpectrum Self-Report (MOODS-SR), and Ruminative Response Scale (RRS).Results: The BPD group was split into subjects with BPD+ mood disorder (MD) or BPD only) . PTSD-criteria fulfillment, MOODS, and RRS scores were significantly higher in both BPD subgroups than in controls, while BPD+MD patients scored significantly higher than the BPD-only group. RRS scores and PTSD-criteria fulfillment were significantly related to the presence of both BPD and BPD+MD, with no effect of MOODS-SR scores.Conclusion: Our findings confirm the presence of a relationship between BPD and the PTSD spectrum, highlighting also a possible role of rumination in BPD psychopathology. Rumination and PTSD symptoms seem to prevail in the effect of mood spectrum in predicting BPD.Keywords: ruminative thinking, borderline personality disorder, post-traumatic stress disorder, mood disorders